From bare life and necropolitics to a feminist care ethic: ageism in the COVID-19 pandemic and future directions - Simmonds, Bethany (Frontiers in Sociology, 2024)
This perspective paper begins with discussing how COVID-19 magnified the pre-pandemic ‘bare life’ conditions which exposed older people’s lives to risks and indignities in the health and social care system. Then, by using the concept of Necropolitics, the life and death decisions, based on age as a proxy measure for population health during the pandemic, are discussed. This discussion includes examples of ‘exceptional’ practices that were implemented in the UK during the first wave, including ‘Do Not Resuscitate’ orders, unsafe hospital discharges, not transferring to hospitals, and denying access to treatment for older people. It then goes on to renew the call for a feminist care ethic to be central to the ways in which our future health and social care systems are configured. Arguing for the need to politically reframe ageing, health and social care provision towards a radical alternative system that rethinks care relations and addresses inequality.